Different Designs of Dual-Focus Perforated Transmitarray Antenna in Near/Far-Field Region - Malhat, H. Abd El-Azem; Zainud-Deen, S.; Hassan, W. (Advanced Electromagnetics, 2016)
Designs of the single-focus and multi-focused transmitarray antennas for the near-field (NF) or/and far-field (FF) applications have been introduced. Perforated dielectric single sheet is used for transmitarray design for simple configuration. Single-focus transmitarray for the far-field and the near-field are obtained. The radiation characteristics of 13×13 unit-cells transmitarray in the near-field and the far-field region have been investigated. A single structure multi-focus transmitarray is designed using the chess-board arrangement of the unit-cells elements. Multi-focus transmitarray for FF/FF, FF/NF, and NF/NF have been designed and investigated. The phase distribution and the corresponding holes radii for the first quadrant of the multi-focus transmitarray are presented. The radiation characteristics of different array configuration have been investigated and analyzed using full-wave simulator CST Microwave Studio.